MODEL INTENSI PENCARIAN INFORMASI DAN INTENSI PEMBELIAN - Muhammad Dharma Tuah Putra Nasution (JUMANT, 2016)
Lenovo company derived from China has successfully acquired IBM in the United States.Lenovo has a superior notebook that was selected as "Best Brand" in Indonesia Best BrandAward 2015. The purpose of this study was to investigate the effect of the country of originimage, product knowledge, and product involvement to search information and purchaseintentions. The study used the model of Structural Equation Modeling. Data was collectedfrom 180 respondents in Medan, Binjai, and Deli Serdang. The study result was found thatthe country of origin image has a positive and significant effect to search information andpurchase intentions. Similarly, consumer product involvement has a positive andsignificant effect to search information and purchase intentions. However, consumerproduct knowledge hasn’t significant effect to search information search and purchaseintentions. We advise using the appropriate media to communicate the informationregarding the products release until to provide knowledge for the society.